Advocating for Enhanced Understanding: Empowering Government Officials with Insights into Village Income Dynamics - Oky, Rachmad; Zaid, Aminuddin (Universitas Negeri Semarang, 2023)
This study advocates for a deeper understanding of village income dynamics among government officials, with a focus on Tarai Bangun Village in Riau, Indonesia. Despite its resource-rich environment, Tarai Bangun grapples with various socio-economic challenges affecting its income generation. Through rigorous research and data analysis, the study seeks to equip government officials with insights into the complexities of village income dynamics, facilitating more informed policy-making and resource allocation. By bridging theory and practice, this advocacy-driven research aims to catalyze sustainable development and prosperity in Tarai Bangun Village and similar communities across Indonesia. Additionally, the study highlights the ongoing development of Kampar District, noting progress but acknowledging room for improvement. Obstacles such as a shortage of skilled human resources, reliance on rental income, insufficient regulatory frameworks for managing village assets, low community engagement, and inadequate accountability for village work plans are identified. Current efforts focus on enhancing human resource capacity, cultivating community mindset shifts, implementing robust regulations for village asset management, and providing training to ensure transparent accountability processes.